An Analysis of the Translation Errors in the Tourism Guide Book "Wonderful Riau Islands" and its Impact on the Visit Interests of Foreign Tourists to the Riau Islands Province - Taufik Afdal; Joko Iswanto; Eka Mayasari (SALEE: Study of Applied Linguistics and English Education, 2022)
This study aims to describe translation error patterns from Indonesian into English found in the Wonderful Kepri Tourism Guide book. The data in this research are the erronously translated words, phrases and clauses. The samples of the data were collected from several pages in the book. Types of errors are classified into syntactic errors including usage, punctuation, grammar, and syntax. Semantic errors include spelling, tenses, addition or omission of word elements, terminology or diction and free translation. With reference to the findings of this study, the researcher provides a more accurate translation in accordance with the Language of Tourism (LoT) specification and in accordance with the original text so that the message delivered reaches the target audience. The findings are expected to serve as a reference for Provincial Tourism Office of Kepulauan Riau to translate tourist guide books accurately and carefully in the hope that the number of tourism visits especially English-speaking tourists increases in the following years ahead.